Renal Replacement Therapy in Children in the Developing World: Challenges and Outcome in a Tertiary Hospital in Southeast Nigeria - Odutola Israel Odetunde; Henrietta Uche Okafor; Samuel Nkachukwu Uwaezuoke; Bertilla Uzoma Ezeonwu; Oluchi Mildred Ukoha (The Scientific World Journal)
A 5-year observational, retrospective study was conducted to evaluate the indications, the availability, the accessibility, the sustainability, and the outcome of children managed for acute kidney injury (AKI) and end stage kidney disease (ESKD) who required renal replacement therapy RRT in Enugu, southeast Nigeria. A total of 64 patients aged 5 months to 16 years required RRT, of which only 25 underwent RRT, giving an RRT accessibility rate of 39.1%. Eleven (44%) patients required chronic dialysis program/ renal transplant, of which only 1 (9.1%) accessed and sustained chronic hemodialysis, giving a dialysis acceptance rate of 9.1%. Fifty (78%) of the patients belonged to the low socioeconomic class. Thirty-three (51.5%) could not access RRT because of financial constraints and discharge against medical advice (DAMA); 6 (9.4%) died on admission while sourcing for funds to access the therapy; 5 (7.8%) died while on RRT; 9 (14.1%) improved and were discharged for follow-up; 1 (1.6%) improved and was discharged to be on chronic dialysis program while awaiting renal transplantation outside the country/clinic follow-up, while the remaining 10 (15.6%) were unable to sustain chronic dialysis program or access renal transplantation and were lost to follow-up. We conclude that RRT remains unaffordable within the subregion.